Peningkatan Kualitas Pendidikan pada Satuan Pendidikan Melalui Perencaan Berbasis Data - Eddy Saputra; Rayung Wulan; Nur Ali; Hasan Özalp (Universitas Indraprasta PGRI, 2025)
Improving the quality of education is the main focus in efforts to create superior and adaptive educational units to the dynamics that occur. One of the strategic approaches currently being promoted by the government is the implementation of Data-Based Planning (PBD). This approach allows educational units to make decisions that are more objective, measurable, and in accordance with real needs in the field. With the effective implementation of Data-Based Planning, educational units are expected to be able to improve the quality of learning, educational services, and the achievement of student learning outcomes in a sustainable manner. The research method used is qualitative with a case study approach that is intended to find out in detail the problems faced. This study aims to examine the implementation of Data-Based Planning in improving the quality of education in the Central Jakarta 1 Senior High School environment, as well as to identify the challenges faced and strategies that can be developed. The results of the study show that although most schools have access to educational data, its use in the planning process is still not optimal. Factors such as low data literacy, limited training, and lack of a reflection-based work culture are the main obstacles. Therefore, it is necessary to strengthen the capacity of human resources and support systems that encourage maximum data utilization in the planning and evaluation of school programs.